FORMATION OF TRANSLATION THEORY - Farmonov Bahodir Dustmurodivich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In this article, the formation of translation studies as a science, its theoretical foundations, subject and its application in linguistics are covered.